Desenvolvimento profissional do professor de música da educação básica : experiências de formação em uma comunidade online - Andrade, Lucila Prestes de Souza Pires de (2024)
In this investigation, teacher education is considered in terms of professional development (Nóvoa, 1992; 1996; Marcelo, 2009), as a process that takes into account teaching and learning experiences both before and during professional practice and includes experiences outside the school environment, such as in the context of an online community. The main objective of the research was to understand how participation in the Musicalização Brasil community provides formative experiences that contribute to the professional development of music teachers in basic education. The secondary objectives were to contextualize the interaction practices in an online community of music teachers; to investigate music teachers' perceptions regarding their professional development experiences in an online community; to analyze the professional development processes in relation to participation in an online community; and to identify the characteristics of professional development for music teachers in this context. The theoretical and methodological framework of the research is based on the understanding that the group where the work was conducted constitutes a community of practice (Wenger, 1998). The research site was an online community created in the form of a group on the WhatsApp messaging app, mostly composed of music teachers working in basic education. The methodology, following a qualitative approach in the format of online ethnographic research (Kozinets, 2014), used communal interaction, online focus groups, interviews, and field notes as means of data collection. The analyses aimed to present the main interaction practices of the community, including recording and sharing lessons, the repertoire of resources and teaching methods, and the multiplicity of knowledge and experiences that characterize teaching. The results highlight the characteristics of professional development in the studied context: mobility, collaboration, coherence, being a support network, focus on practice, motivation and training autonomy. The announced thesis is that the professional development of basic education music teachers in an online community is influenced by a variety of everyday actions and interactions, whether in formal initiatives or informal opportunities; it is particular to each teacher, based on the use they make of their experiences as a participant; resides in the encounters: with what others share and with their own ideas and experiences narrated in this and other spaces, and awakened in each teacher through these interactions.